Zooarchaeology and Field Ecology : A Photographic Atlas - Broughton, Jack M.; Miller, Shawn (Shawn D.) (Book collections on Project MUSE., 2016)
"The only field guide and laboratory manual to cover both the osteology and the natural history of western North American vertebrates in a single volume This photographic atlas, developed over twenty years of teaching in the field, expedites the work of the zooarchaeologist by integrating both osteology and wildlife ecology into a single volume. Zooarchaeology, the study of animal remains found at archaeological sites, is interdisciplinary in nature, requiring students and researchers to not only master the technical skills of identifying fragmentary bones and teeth but also to develop a deep understanding of the taxonomy, natural history, behavior, and ecology of the species identified. Until now, these topics have always been treated separately. This book is the only field guide and laboratory manual to combine animal ecology and natural history with the detailed osteology of all the vertebrate classes (fishes, amphibians, birds, and mammals) and all the primary orders native to western North America. Skeletal images are shown at a variety of magnifications and views and are accompanied by photographs of the animals in their characteristic habitats"--